2019
DOI: 10.1002/csr.1721
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the level of environmental disclosures in sustainability reports: Case of climate risk disclosure by Brazilian companies

Abstract: In addition to sustainability issues, companies are being asked to disclose information on climate change risks in order to inform investors and stakeholders. However, despite the growing number of studies on corporate environmental disclosure, there are few studies on risks and opportunities in relation to climate change. This study investigated the extent and content of climate risks information disclosure provided in the sustainability reports of firms listed on the Brazilian Stock Exchange (BM&FBovespa) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
90
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(152 citation statements)
references
References 73 publications
(107 reference statements)
11
90
0
13
Order By: Relevance
“…They point out that although corporate political connections can influence companies to more actively disclose environmental information, it can also mask political rent-seeking in the guise of protecting the environment. In addition, the literature indicates that company characteristics such as financial leverage, capital requirements, and equity structure also impact environmental information disclosure [15][16][17][18].…”
Section: Company Characteristicsmentioning
confidence: 99%
“…They point out that although corporate political connections can influence companies to more actively disclose environmental information, it can also mask political rent-seeking in the guise of protecting the environment. In addition, the literature indicates that company characteristics such as financial leverage, capital requirements, and equity structure also impact environmental information disclosure [15][16][17][18].…”
Section: Company Characteristicsmentioning
confidence: 99%
“…Also, larger firms, due to their size, can take on the extra voluntary disclosure cost that come with disclosing more environmentally related issues, hence the positive coefficient. Beyond their ability to take on the extra voluntary disclosure cost, larger firms tend to have a greater “impact on social expectations because they have more stakeholders than small companies” (Kouloukoui et al, , p. 9).…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Therefore, highly leveraged firms will disclose less information. Some studies supported this view and found a negative relation between financial leverage and environmental disclosure (Brammer & Pavelin, 2006;Dejean, 2009;Andrikopoulos & Kriklani, 2013;Singhania & Gandhi, 2015;Deswanto & Siregar, 2018;Kouloukoui et al, 2019). However, another empirical research group did not find any significant relation between financial leverage and environmental disclosure (Cormier & Gordon, 2001;Freedman & Jaggi, 2005;Brammer & Pavelin, 2008;Pahuja, 2009;Sun et al, 2010;Clarkson et al, 2011;Michelon & Parbonetti, 2012;Wang et al, 2012;Setyorini & Ishak, 2012;Lu & Abeysekera, 2014;Akbaş, 2014;Rover et al, 2015;Braam et al, 2016;Ahmadi & Bouri, 2017;Chandok & Singh, 2017;Elshabasy, 2018;Kılıç & Kuzey, 2019;Akbaş & Canikli, 2019).…”
Section: Financial Leveragementioning
confidence: 99%
“…Hackston & Milne, 1996;Patten, 2002;Brammer & Pavelin, 2006;Liu & Anbumozhi, 2009;Huang & Kung, 2010;Wang et al, 2012;Lu, 2014;Akbaş, 2014;Fontana et al, 2015;Welbeck et al, 2017;Ismail et al, 2018;Ofoegbu et al, 2018;Ashfaq & Rui, 2019). However, some studies reported an insignificant relation between industry type and environmental disclosure (Braam et al, 2016;Ahmadi & Bouri, 2017;Kolsi & Attayah, 2018;Kılıç & Kuzey, 2019;Akbaş & Canikli, 2019;Kouloukoui et al, 2019).…”
Section: Industry Typementioning
confidence: 99%